Defect-rich and ultrathin N doped carbon nanosheets as advanced trifunctional metal-free electrocatalysts for the ORR, OER and HER. Issue 1 (5th December 2018) - Jiang, Hao; Gu, Jinxing; Zheng, Xusheng; Liu, Min; Qiu, Xiaoqing; Wang, Liangbing; Li, Wenzhang; Chen, Zhongfang; Ji, Xiaobo; Li, Jie
Abstract : Defect-rich and ultrathin N doped carbon nanosheets exhibited low overpotentials and robust stability for simultaneous ORR, OER and HER. Abstract : Rational design and facile preparation of non-noble trifunctional electrocatalysts with high performance, low cost and strong durability for the oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are highly demanded, but remain as a big challenge. Herein, we report a spontaneous gas-foaming method to prepare nitrogen doped ultrathin carbon nanosheets (NCNs) by simply pyrolysing a mixture of citric acid and NH4 Cl. Under the optimized pyrolysis temperature (carbonized at 1000 °C) and mass ratio of precursors (1 : 1), the synthesized NCN-1000-5 sample possesses an ultrathin sheet structure, an ultrahigh specific surface area (1793 m 2 g −1 ), and rich edge defects, and exhibits low overpotential and robust stability for the ORR, OER and HER. By means of density functional theory (DFT) computations, we revealed that the intrinsic active sites for the ORR, OER and HER are the carbon atoms located at the armchair edge and adjacent to the graphitic N dopants. When practically used as a catalyst in rechargeable Zn–air batteries, a high energy density (806 W h kg −1 ), a low charge/discharge voltage gap (0.77 V) and an ultralong cycle life (over 330 h) were obtained at 10 mA cm −2 for NCN-1000-5. This work not only presents a versatile strategy to develop advanced carbon materials with ultrahigh specific surface area and abundant edge defects, but also provides useful guidance for designing and developing multifunctional metal-free catalysts for various energy-related electrocatalytic reactions.